Poisoned ivies : the inside account of the academic and moral rot at America's elite universities - Stefanik, Elise, 1984- (Threshold Editions, an imprint of Simon & Schuster, 2026)
"For decades, conservatives have warned about the decline of higher education. Now, for the first time in modern history, Americans are taking action. Congresswoman Elise Stefanik, a Harvard alumna herself, lit the fuse when she posed basic questions to the presidents of Harvard, MIT, and the University of Pennsylvania, such as: Does calling for the genocide of Jews violate your university's rules on bullying and harassment? Their inability to answer with moral clarity sparked a national reckoning causing multiple Ivy League presidents to resign. It was the most-watched Congressional hearing of all time. But that was just the beginning. Poisoned Ivies delivers an unflinching account of what has gone wrong on America's college campuses. Stefanik exposes how the nation's most prestigious institutions abandoned their founding ideals of freedom of thought, open debate, and academic excellence, and instead embraced a culture of censorship, radical leftist groupthink, antisemitism, and moral cowardice that has spread far beyond campus walls to every corner of American life. Both a damning exposé and a blueprint for reform, Poisoned Ivies is a timely story of courage and conviction and the power of one voice to challenge the status quo in American higher education and delivers a long-overdue reckoning. A must-read for anyone concerned with the fight for our nation's soul." --